Assessing the landscape of ovarian serous borderline tumors. Issue 3 (18th January 2019) - Messini, Irini; Doulgeraki, Triada; Chrysanthakis, Dimitris; Yiannou, Petros; Gavresea, Theofani; Papadimitriou, Christos; Panoskaltsis, Theodoros; Voulgaris, Zannis; Vlachos, Athanassios; Pavlakis, Kitty
Abstract : Aim: To compare distinct clinicopathological features between atypical proliferative serous tumors and non-invasive low-grade ovarian serous carcinomas. Methods: Our study group comprised 203 cases of serous borderline tumors sub-classified as atypical proliferative serous tumors or as non-invasive low-grade serous carcinomas. All pathological features related to borderline tumors were re-evaluated by two gynecological pathologists. Data concerning recurrences and survival were retrieved from the medical records of the patients. Results: When comparing atypical proliferative serous tumors to non-invasive low-grade serous carcinomas, the latter were statistically related to advanced stage at diagnosis, bilateral disease, exophytic pattern of growth, microinvasive carcinoma, and the presence of invasive implants. In univariate analysis, recurrences were statistically related to the exophytic pattern of growth, to microinvasion, and to the presence of implants (both invasive and non-invasive). Nevertheless, in multivariate analysis, only microinvasion and the presence of invasive implants were related to recurrence. Women who eventually succumbed to the disease were only those with invasive implants. Their ovarian tumor was either a non-invasive low-grade serous carcinoma or an atypical proliferative serous tumor with 'minimal' micropapillary pattern. Neither lymph node involvement nor endosalpingiosis seemed to influence the course of the disease. Conclusions: The results of our study underline the increased possibility of non-invasive low-grade serous carcinomas to be related with features indicative of aggressive behavior as opposed to atypical proliferative serous tumors. Nevertheless, irrespective of tumor histology, the presence of invasive implants and microinvasion were the only independent prognostications of recurrence.